Hambatan Aksesibilitas Masyarakat terhadap Hak Keadilan Perdata - Wirastomo, Rizky; Muhammadin, Fajri Matahati; Wijayanta, Tata (Jurnal Hukum IUS QUIA IUSTUM, 2017)
Right to seek adjudication of conflicts qualifies as human rights. However, we find that whenever the economical value of a dispute is insignificant in comparison towards court’s fees, this rights tend to be infringed. Judicial reform with a sole interest of a faithful recognition of human rights is needed.